AN ANALYSIS ON THE EFFECT OF AUDIT TENURE, CORPORATE GOVERNANCE STRUCTURE, AND SIZE OF AUDIT FIRM TO THE FINANCIAL INTEGRITY STATEMENTS - Abidin, Iqbal Zainul; RUSTAM, AKIE RUSAKTIVA (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research attempts to obtain empirical evidence of the effect of audit tenure, corporate governance structure (independent commissioner, audit committee, managerial ownership, institutional ownership) and the size of audit firm to the financial integrity statement of manufacturing companies in Indonesia. The dependent variable used in this research is financial integrity while the independent variables are audit tenure and corporate governance structure which will be analyzed by using independent commissioner ownership, audit committee, managerial ownership, institutional ownership, and size of the audit firm. The measurement of financial integrity will be done through conservatism analysis. The samples in this research are manufacturing companies listed in BEI during 2011-2014 period. The data collection is conducted using purposive sampling method. The total sample used in this research are 120 companies. The data analysis technique method of this research utilizes multiple linear regression. The results  showed  that  audit  tenure  and  size  of  audit  firm  do  not  influence  the integrity of financial statement significantly.    Keywords : financial integrity, audit tenure, corporate governance, size of audit firm